2019
DOI: 10.1002/app.48146
|View full text |Cite
|
Sign up to set email alerts
|

Role of the degree of acetalization on dynamic mechanical properties of polyvinyl butyral/carbon nanotube composites

Abstract: In this work, polyvinyl butyral (PVB) nanocomposites reinforced with 0.1-1.0 wt % of pristine [carbon nanotube (CNT)] or oxidized (CNTO) multiwalled CNTs were synthesized via in situ polymerization. It was found that the presence of the reinforcement during the synthesis altered the degree of acetalization of PVB. Dynamic mechanical analyses showed that PVB nanocomposites containing 0.5 wt % of pristine CNT had the best adhesion factor, with increases of about 30% in the storage modulus. On the other hand, PVB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…AD values were obtained in previous works. [13,27] Spectra were recorded using a 400 MHz Bruker Advanced spectrometer, using DMSO-d6 as solvent, without internal standard. The analyses of the fracture surfaces of tensile-tested specimens were performed on a fieldemission scanning electron microscope (FE-SEM) JEOL-6701F, after gold sputtering.…”
Section: Characterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…AD values were obtained in previous works. [13,27] Spectra were recorded using a 400 MHz Bruker Advanced spectrometer, using DMSO-d6 as solvent, without internal standard. The analyses of the fracture surfaces of tensile-tested specimens were performed on a fieldemission scanning electron microscope (FE-SEM) JEOL-6701F, after gold sputtering.…”
Section: Characterizationsmentioning
confidence: 99%
“…The values of acetalization degree (AD), corresponding to the vinyl butyral cotent, were calculated from previous studies [13,27] by equation (1) where A CH2 and A CH3 are the total areas of methylene and methyl protons, respectively. [1] The calculated values of the acetalization degree are shown in Table 2.…”
Section: 1 Acetalization Degreesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoepfner et al. studied the corrosion influence of carbon nanotube (CNT) or oxidized (CNTO) multiwalled CNTs with PVB via in situ polymerization [23] . The obtained results showed that PVB possessed tremendous potential in the field of anti‐corrosion coating.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, filtration coating as a form of direct loading to fabricate CNT polymer composite membranes has attracted a lot of research attention. 15,16 Apart from the filter coating method, in situ polymerization 17 and self-assembly 18 are other preparation methods for CNT polymer composite membranes. Compared with the above methods, CNT mats prepared by the filter coating method take full advantage of CNTs at the membrane/water surface because the CNTs are not impregnated in the membrane polymer matrix.…”
Section: Introductionmentioning
confidence: 99%